Anterior-Segment Retinoblastoma Mimicking Pseudoinflammatory Angle-Closure Glaucoma: Review of the Literature and the Important Role of Imaging - Saket, R.R.; Mafee, M.F. (American Journal of Neuroradiology, 2009)
A 7-year-old boy presented with angle-closure glaucoma, initially presumed to be idiopathic. A ciliary body mass was later detected on MR imaging, suggestive of medulloepithelioma but pathologically proved to be diffuse infiltrating retinoblastoma. We discuss the patient management and review the literature, with emphasis on the role of CT and MR imaging in evaluating pediatric angle-closure glaucoma and in influencing the management of patients with retinoblastoma and medulloepithelioma.